Cephalosporin susceptibility of Staphylococcus aureus strains isolated from commercial rabbit and goats farms in Spain - Badillo, Elena; Escudero, Elisa; Galecio, Juan Sebastián; Hernandis, Verónica; Marin, Pedro (Veterinaria Italiana, 2023)
Antimicrobial drug resistance is an important problem that challenges veterinary clinicians to provide effective treatments without further spreading resistance to other animals and people. The most commonly used pharmacodynamic parameter to define potency of antimicrobial drugs is minimum inhibitory concentration (MIC). The aim of this study was to evaluate the antibiotic susceptibility of thirty-six strains of Staphylococcus aureus isolated from dairy goats with mastitis and rabbits with chronic staphylococcosis. Four cephalosporins were tested: cephalexin, cephalotin, cefonicid and ceftiofur. MIC tests were performed according to the microdilution broth method. The calculated values of sensitivity in goats and rabbits were 66.67% and 72.22% for cephalexin, 72.22 % and 94.44% for cefonicid, 77.78% and 94.44% for cephalotin and 77.78% and 100% for ceftiofur, respectively. For all antibiotics, MIC90 of S. aureus from rabbits were lower than MIC90 from goats. These data suggest that more antibiotics are used in goat milk production than in rabbit farming. According to MIC values obtained in this study, ceftiofur and cephalotin may be the best option for treating S. aureus infections in lactating goats. For rabbits, ceftiofur showed lowest MIC values, therefore, it could be an alternative to treatment the infections caused by S. aureus in this species.